2022
DOI: 10.1002/cnma.202200013
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐State and Dynamic Bioanalysis using Carbon Quantum Dot‐based Luminescence Probes

Abstract: Carbon quantum dots (CQDs) with excellent biocompatibility, tunable emission and designable surface composition have been widely applied for luminescent sensing of diverse biological targets. In addition to homogeneous bioanalysis, dynamic bioanalysis of biological analytes is also achieved with the combination of single-particle imaging technique. In this review, we majorly conclude the recently adopted steady-state and dynamic bioanalysis based on CQD luminescence probes. The synthesis and lumines-cence mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Compared with the O3-type material, the P2-type Na x TMO 2 has a more stable structure and higher ionic conductivity. [20][21][22] P2-type Na 0.67 Ni 0.33 Mn 0.67 O 2 (NNMO), as a representative manganese-based layered oxide cathode, shows a high theoretical specic capacity (173 mA h g −1 ) and high average discharge voltage (3.6 V). 23 Due to the existence of the Ni 2+ /Ni 4+ redox couple, it undergoes a series of phase transitions from P2 to O2 structures during charge and discharge processes, which results in severe capacity attenuation during the cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the O3-type material, the P2-type Na x TMO 2 has a more stable structure and higher ionic conductivity. [20][21][22] P2-type Na 0.67 Ni 0.33 Mn 0.67 O 2 (NNMO), as a representative manganese-based layered oxide cathode, shows a high theoretical specic capacity (173 mA h g −1 ) and high average discharge voltage (3.6 V). 23 Due to the existence of the Ni 2+ /Ni 4+ redox couple, it undergoes a series of phase transitions from P2 to O2 structures during charge and discharge processes, which results in severe capacity attenuation during the cycle.…”
Section: Introductionmentioning
confidence: 99%
“…According to the fitting, the lifetime was calculated to be 10.6 ns, which is longer than many reported values of CDs [ 45 ]. It is reported that the surface state and surface functional groups are important to the fluorescence behavior of CDs, and the abundant C–O/C–N/C=N groups in high oxidation state may produces more of smaller energy gaps and induce diverse electron transition pathways [ 26 ]. To understand the surface composition, the FT-IR spectra of PD-CDs were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical energy density of the cathode material is the upper limit of the energy density of the battery cell, and the cathode material affects the power density of the SIBs by affecting the ability to accommodate sodium ions and the fluency of the transmission channel. [69][70][71] At the same time, the loss of active substances in the cathode material and the impurity composition will affect the life of the battery. At present, the mainstream cathode materials for SIBs mainly include transition metal oxide materials, polyanionic materials and prussian blue materials.…”
Section: Selection Requirements and Common Cathode Materials For Sodi...mentioning
confidence: 99%